Nutritional properties of Europen eel (Anguilla anguilla) bone peptide-calcium and its apoptosis effect on Caco-2 cells - Hui Teng; Yuewei Qian; Xiaoyun Fan; Hui Cao; Yuting Tian; Lei Chen (Food Science and Human Wellness)
The present study aimed at making a rational usage for European eel bone by-products by preparing Europen eel bone peptide chelated calcium (EBPC-Ca). Nutritional properties and bioactivity of EBPC-Ca were evaluated. Results showed that nutritional properties of calcium ions will cause intra- and inter-molecular folding and aggregation of peptide to uniformly form EBPC-Ca chelate. The chelated compound of EBPC and calcium ion triggered a strong apoptosis in heterogeneous human epithelial colorectal adenocarcinoma (Caco-2) in concentration- and time-dependent manners. Western blot analysis revealed that the EBPC-Ca induced apoptosis may be the result of a blocked autophagy flux through mitochondrial-dependent pathway. Additionally, the increase in FGF-23 protein expression inhibited the absorption of calcium ions and alleviated cell apoptosis. It was also found that the cell apoptosis occurs with significant increases in the levels of reactive oxygen species (ROS) and Ca2+ in the cells, indicating the anti-tumor potential of EBPC-Ca may involve multiple channels.